Drop jumps versus sled towing and their effects on repeated sprint ability in young basketball players - Zagatto, A. M.; Claus, G. M.; Dutra, Y. M.; de Poli, R. A.; Lopes, V. H. F.; Goodall, S.; Loturco, I.; Boullosa, D. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background The aim of the investigation was to compare the occurrence of post-activation performance enhancement (PAPE) after drop jumps, or heavy sled towing, and the subsequent effect on repeated sprint ability (RSA).